Utilization of Indian gooseberry (Phyllanthus emblica L.) as foods - Cheekham, Phuriwat; Kaewsritong, Jiraphat; Srikaeo, Khongsak (Journal of Food Technology Research, 2024)
This study aimed to investigate the consumption of amla as a food by conducting a thorough literature analysis and a field survey with unstructured, in-depth interviews. Amla or Indian gooseberry (Phyllanthus emblica L.) is rich in phytochemicals, and their pharmaceutical potentials have been extensively reported. However, their utilization as foods is not well documented. Thai recipes use whole or minced fresh amla fruits as an ingredient in some spicy dishes, such as chili pastes, soups, and salads. Like other Asian countries, amla could be processed into products such as juice, preserves, pickles, and dried amla. Ten amla dishes and products were selected for evaluation of their ascorbic acid contents and antioxidant properties (total phenolic compounds, total flavonoids, DPPH, and FRAP assays). High-heat processing resulted in a marginal reduction of ascorbic acid in amla dishes and products. Processing methods also affected antioxidant activities, and they varied depending on processing conditions and product types. The processing of amla into juice slightly decreased antioxidant activities. Thai foods that used amla as an ingredient exhibited less antioxidant activity than those made of fresh amla. The antioxidant activities of pickled and preserved amlas were substantially diminished due to their high salt and sugar content. On the contrary, dried amla demonstrated enhanced antioxidant activities as a result of its reduced moisture content and the presence of concentrated phytochemicals. Given its substantial phytonutrient content and lack of utilization, the results obtained from this research contribute to the promotion of amla as a valuable food ingredient.